Effect of Learning Achievement of the Eye of Productive Training, Prakerin Experience, and Interests in Student Readiness Entering the World of Work - Dita Nur Faizah; Aniek Indrawati (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
This study is a quantitative research by using descriptive and ex-post facto. The purpose of this research is to know how: (1) the description of learning achievement, description of internship experience, description of working interest, and description of working readiness; (2) the effect of productive learning achievement, internship experience, and working interest partially on the readiness of work for the students of SMK Negeri 1 Kraksaan Probolinggo. Data collection techniques used are questionnaire and documentation method. The sampling technique used is proportional random sampling. The result of the analysis shows that: (1) student learning achievement of productive, student internship experience, students working interest, and readiness of student work is in good category; (2) there is a negative and not significant influence between learning achievement of productive education and training on job readiness; (3) there is a positive but insignificant influence between internship experience on job readiness; (4) there is a positive but not significant influence between the interest of work to the readiness of class XII business management students in SMK Negeri 1 Kraksaan Probolinggo.